Is COP 31 2026 Going to be a Sweet Spot for Renewables Transition? (CONECT. International Scientific Conference of Environmental and Climate Technologies, 2026)
As we have leaped into 2026, it becomes imperative for the climate change mitigation machinery to tighten the purpose and practice for this year COP 31 2026 scheduled to be held later this year. What has the Conference of Parties (COP) given us all these years, false promises and futile negotiations with agreement not turning into enforcement for deployment and implementation. Putting the very purpose of COP into a questionable virtue of conduct. COP 30 2025 left behind non-consensus on climate multilateralism, fossil fuels phase out and uneven positioning of climate change adaptation and resilience. This has raised a big question as resilience as a best practice or a failing practice and putting straightforward practice and call as an immediate priority. Through this paper, a question to raise the deployment machinery is being put forth as “Is COP 31 2026 going to be a "SWEET SPOT" for renewables transition or whether the uneven shift will remain a "GREY SPOT" as Corporates are not going to shed their virtue of lobbying for fossil fuels in business. Why are corporate businesses allowed an entry to the Conference of Parties when it is a scientific consideration of processes and procedures for negotiations which later businesses need to implement on the basis of the enforcement and deployment machinery being agreed for. The corporates not just demean the purpose of the summit but downgrade the shift in transition towards renewables, as for them it is business as usual but for climate change action it only seeks beyond business "New Normal" with strengthened penetrative and transformative scientific solutions. Civil Societies over the years have been pushing hard for climate multilateralism and corporations still relish the subsidies on fossil fuels at the cost of the planet and people. The developed countries have majorly submitted their Nationally Determined Contributions (NDCs) however developing countries are falling short in practice and purpose for preparing the NDCs road map as it is failing in its strategy and target setting as well as procedural modalities. Of the 200+ countries which have ratified the Paris Agreement to reduce the global warming and temperature to well below 1.5 degrees centigrade, hardly few among them have been able to seize the tipping point for emission reductions as well as reducing the locally enabling heat Islands. Local Led Adaptation and Mitigation is key to comply with the Paris Agreement otherwise the temperature effect shall downgrade the planet and people together. The paper highlights and raises critical issues of concern on Non-confirmity to climate targets set as per NDCs as not all countries have uniformly submitted their NDCs which weakens the strength and penetration of climate change strategy across countries, cities and communities. The NDCs should include contributions under three criteria for : Country level, City level and Communities level and put Monitoring Reporting and Verification (MRVs) aligned and integrated with Monitoring, Reporting, Evaluation and Learning (MREL) framework as outcomes from every mitigation effort is learning from improving the best practices and benchmarking our own climate commitments and create self sufficient infrastructure for commitments to transitioned into transformative actions.